A Rare Indolent Course of Rhinocerebral Mucormycosis - Aleksandr Khudyakov; Rafsan Ahmed; Chi Doan Huynh; Amir Dehghani; Zhonghua Li; Michael Rose (Case Reports in Infectious Diseases)
Mucormycosis is a highly invasive and rapidly progressing form of fungal infection that can be fatal. The infection usually begins after oral or nasal inhalation of fungal spores and can enter the host through a disrupted mucosa or an extraction wound. The organism becomes pathogenic when the host is in an immunocompromised state. There are several clinical presentations of mucormycosis including rhinocerebral, pulmonary, cutaneous, gastrointestinal, disseminated, and miscellaneous forms. The most common clinical presentation of mucormycosis is the rhinocerebral form which has a high predilection for patients with diabetes and metabolic acidosis. An indolent disease course taking weeks to months of this infection is rare making it difficult to diagnose. Therefore, early detection and prompt treatment with surgical and antifungal therapy are very important in achieving good treatment outcomes.